The isolation and characterization of cytochrome c nitrite reductase subunits (NrfA and NrfH) from Desulfovibrio desulfuricans ATCC 27774 - Almeida, Maria Gabriela (2008)
Eur. J. Biochem. 270, 3904–3915 (2003)